Gambaran Pola Makan dan Kadar Asam Urat pada Lansia Menggunakan Metode Point of Care Testing - Agus Sudrajat; Nova Octaviana (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Uric acid is a normal thing that everyone has in the body. Because uric acid is a natural metabolic excretion from the body that comes from the breakdown of purines. One of the causes of gout is an unhealthy diet. The elderly are the age most susceptible to gout. A person can be said to be elderly (elderly) if he is 65 years or older. This research used total sampling research methods and stick or POCT method sampling in the Paku Haji village community aged 40 - 60 years, totaling 30 samples which were carried out on July 10 - July 11 2024, with results differentiated based on age and gender. Uric acid levels aged 40 – 60 years were found to be normal in 21 people (70%) and high in 9 people (30%). Uric acid levels based on gender were found to be normal in 18 people (60%) and high in 12 people (40%).